Peak performance : - Ferrett, Sharon K. (McGraw-Hill, 2006)
This best-selling text presents new and returning college students with practical, hands-on methods of increasing their performance inside and outside the classroom. It helps them make the connection between their academic efforts and their job and life skills. They learn a variety of personal productivity skills related to positive work and study habits, as well as creative problem-solving, organizational, and interpersonal skills.